Distribution and consumption of fluorite and translucent beads in the Iberian peninsula from 6th to 2nd millennia BC - Garrido-Cordero, José Ángel (2021)
Translucent minerals were valued in prehistoric societies for their rarity and socially used as highly symbolic elements. This work addresses the use and nature of Iberian translucent beads. We present the results of chemical (Raman spectroscopy, portable X-ray fluorescence, X-ray diffraction and visible (Vis)/near-infrared (NIR) spectroscopy) and contextual analyses and provide a review of the archaeological literature on the manufacture and use of translucent items during Iberian Late Prehistory. A total of 54 translucent beads from 47 sites, primarily burials, were analyzed; 33 were made from fluorite, while the remaining 21 were made of diverse translucent minerals (calcite, quartz and different silicates). The scarcity of translucent items in the archaeological record, the regional and supraregional scale of its exchange, and its recursive association to other valuables in singular contexts reinforces the idea that their owners/wearers enjoyed a high status.